A novel temperature‐tolerant foamed resin for enhanced oil recovery. Issue 10 (22nd October 2018) - Hou, Baofeng; He, Hong; Jia, Ruixiu; Fu, Meilong; Cao, Yanbin; He, Shaoqun; Luo, Liwen; Huang, Youqing
ABSTRACT: The synthesis and performance of a novel temperature‐tolerant foamed resin for enhanced oil recovery were investigated using various methods, including infrared, NMR, scanning electron microscopy (SEM), and displacement experiments. Polycondensation of furfuryl alcohol prepolymers was confirmed by the infrared and NMR results. The poor temperature tolerance of furfuryl alcohol prepolymers after gelation at high temperatures is mainly due to the fracture of furan rings. The addition of ester additives is an effective method of increasing the temperature tolerance of the prepared foamed resins and can effectively reduce the weight‐loss rate of the polycondensation products. The SEM results show that the skeleton structure of the foamed resin remains intact after high‐temperature treatment. Thus, the novel plugging agent system has excellent thermal stability and still has a high strength (>0.8 MPa) after high‐temperature aging treatment for 40 days, giving the prepared foamed resin a good plugging performance (plugging rate > 91%) at 250 °C. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47161. Abstract :